2021
DOI: 10.1007/s00401-021-02316-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiple system atrophy-associated oligodendroglial protein p25α stimulates formation of novel α-synuclein strain with enhanced neurodegenerative potential

Abstract: Pathology consisting of intracellular aggregates of alpha-Synuclein (α-Syn) spread through the nervous system in a variety of neurodegenerative disorders including Parkinson’s disease, dementia with Lewy bodies, and multiple system atrophy. The discovery of structurally distinct α-Syn polymorphs, so-called strains, supports a hypothesis where strain-specific structures are templated into aggregates formed by native α-Syn. These distinct strains are hypothesised to dictate the spreading of pathology in the tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 123 publications
(208 reference statements)
3
60
0
Order By: Relevance
“…Our findings pave the way for future studies to address the molecular mechanisms underlying the ability of α-synuclein from different patients with MSA to drive higher versus lower seeding. Indeed, our results support a model whereby the heterogeneity observed both between different brain regions and between different MSA patients might be due to differences in the cellular environment 6,8 and to the presence of posttranslational modifications 9 and other cofactors, such as p25α 33 , that may confer a selective pressure for one α-synuclein conformation over another 6 .…”
Section: Discussionsupporting
confidence: 79%
“…Our findings pave the way for future studies to address the molecular mechanisms underlying the ability of α-synuclein from different patients with MSA to drive higher versus lower seeding. Indeed, our results support a model whereby the heterogeneity observed both between different brain regions and between different MSA patients might be due to differences in the cellular environment 6,8 and to the presence of posttranslational modifications 9 and other cofactors, such as p25α 33 , that may confer a selective pressure for one α-synuclein conformation over another 6 .…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, it has been shown that oligodendrocytes, but not neurons, phenoconvert LB-like α-syn fibrils into a GCI-like strain, highlighting the fact that the oligodendroglial intracellular milieu determines how MSA-associated α-syn strains are generated [ 130 ]. Supporting these findings, it has been found that sub-stoichiometric concentrations of oligodendroglial protein p25α redirects α-syn aggregation into a unique α-syn/p25α strain with a different structure and enhanced in vivo neurodegenerative properties [ 48 ]. Taken together, these observations highlight the importance of both misfolded seeds and intracellular milieu in the formation of α-syn strains.…”
Section: α-Syn Cell-to-cell Propagationmentioning
confidence: 89%
“…However, it is widely accepted that α-syn primarily occurs as an intrinsically disordered monomer in the cytosol [ 34 ], with few tertiary interactions between the C-terminus and the central hydrophobic NAC region and the N-terminus of the protein [ 35 , 36 ]. A wide variety of conditions have been found to induce α-syn misfolding and aggregation in vitro, including acidic pH [ 37 , 38 ], increased temperature [ 37 ], molecular crowding [ 39 ], divalent and trivalent metal ions such as aluminum, copper(II), iron(III), cobalt(III) and manganese(II) [ 40 ], organic solvents [ 41 ], lipids with high solubility in aqueous solution and short hydrocarbon chains [ 42 ], heparin and other glycosaminoglycans [ 43 ], polycations [ 44 ], pesticides [ 45 ] and α-syn binding proteins [ 46 , 47 , 48 ]. In addition, α-syn can undergo extensive post-–translational modifications (PTMs) that are known to modulate its neurotoxicity and its propensity to aggregate, including phosphorylation [ 49 , 50 , 51 , 52 ], ubiquitination [ 53 , 54 ], nitration [ 55 , 56 ], sumoylation [ 57 , 58 ], truncation [ 59 , 60 ] and N–terminal acetylation [ 61 , 62 ].…”
Section: α-Syn Aggregation and Cytotoxicitymentioning
confidence: 99%
See 2 more Smart Citations